Further Evidence on the Link between Finance and Growth : An International Analysis of Community Banking and Economic Performance - Berger, Allen N.; Hasan, Iftekhar; Klapper, Leora F. (World Bank, Washington, DC, 2014)
The authors contribute to both the finance-growth literature and the community banking literature by testing the effects of the relative health of community banks on economic growth, and investigating potential transmission mechanisms for these effects using data from 1993-2000 on 49 nations. Data from both industrial and developing nations suggest that greater market shares and efficiency ranks of small, private, domestically-owned banks are associated with better economic performance, and that the marginal benefits of higher shares are greater when the banks are more efficient. Only mixed support is found for hypothesized transmission mechanisms through improved financing for small and medium enterprises or greater overall bank credit flows. Data from developing nations are also consistent with favorable economic effects of foreign-owned banks, but unfavorable effects from state-owned banks.